PENGARUH KEPUASAN PASIEN, PERCEIVED VALUE, DAN PERCEIVED IMAGE TERHADAP LOYALITAS PASIEN PADA INSTALASI REHABILITASI MEDIK RSUD DR. R. SOSODORO DJATIKOESOEMO BOJONEGORO - administrator administrator; Meitha Rahardianty; Woro Utari; C. Sri Hartati (Jurnal Manajerial Bisnis, 2019)
The purpose of this research is to describe about patient loyalty, perceived value, perceived image, andpatient satisfaction in Medical Rehabilitation Installation RSUD Dr. R. Sosodoro DjatikoesoemoBojonegoro; analyzing of the effect of patient satisfaction, perceived value, and perceived image partiallyto patient loyalty; and analyzing of the effect of patient satisfaction, perceived value, and perceived imagesimultaneously to patient loyalty of Medical Rehabilitation Installation RSUD Dr. R. SosodoroDjatikoesoemo Bojonegoro. This researchÔÇÖs type is categorized as explanatory research and usingquantitative research approach. Population in this research is all patient who treatment at MedicalRehabilitation Installation RSUD Dr. R. Sosodoro Djatikoesoemo Bojonegoro. The sampling techniqueusing incidental sampling, ie anyone who by chance met with researchers can be used as a sample, whichdetermined 100 people. The result of the research shows that the condition of perceived value, perceivedimage, and patient loyalty in good category, just only patient satisfaction in good enough category.Patient satisfaction, perceived value, and perceived image partially each have a significant effect onpatient loyalty Medical Rehabilitation Installation RSUD Dr. R. Sosodoro Djatikoesoemo Bojonegoro.Simultaneously, patient satisfaction, perceived value, and perceived image have a significant effect onpatient loyalty.Keywords: patient satisfaction, perceived value, perceived image, and patient loyalty